THE EFFECT OF IMPLEMENTING SOCIODRAMA TECHNIQUE GROUP GUIDANCE SERVICES TO IMPROVE THE MORAL OF STUDENTS OF SMP NEGERI 9 MEDAN - Nurhalimah, Nurhalimah; Jamila, Jamila (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aims to determine the effect of Information Services to Increase the Emotional Intelligence of Class X Students at SMK Tamansiswa Medan for the 2023/2024 Academic Year.